Repair method of retired lithium iron phosphate positive electrode material
By using tea polyphenols and lithium salts and combining with hydrothermal method to repair the decommissioned lithium iron phosphate positive electrode material, forming an aluminum phosphate/lithium phosphate composite coating, solving the problems of complicated processes and high energy consumption in the existing recycling process, and achieving efficient repair and performance improvement of the material.
Patent Information
- Application Number
- CN202411705815.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing retired lithium iron phosphate positive electrode material recycling process has problems such as complicated processes, high energy consumption, easy to cause secondary pollution and low added value of recycling products.
Tea polyphenols are used as electron donors, combined with lithium salts and aluminum salts and other materials, and the decommissioned lithium iron phosphate positive electrode material is repaired by hydrothermal method to form an aluminum phosphate/lithium phosphate composite coating to fill the missing parts of the surface carbon layer and improve the electrochemical performance of the material.
The components and structure repair of waste lithium iron phosphate are achieved, the circulation stability and energy density of the material are improved, the process cost and energy consumption are reduced, and the process is simple and environmentally friendly.
Smart Images

Figure CN119581720A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a method for repairing retired lithium iron phosphate positive electrode materials. Background Art
[0002] Lithium iron phosphate has been widely used as the positive electrode material of lithium-ion batteries in the past few years due to its advantages such as high safety, low cost and long cycle life, and occupies a large share of the positive electrode material market for new energy vehicle power batteries. With the continuous retirement of large quantities of lithium iron phosphate power batteries, in the next few years, a large amount of waste lithium iron phosphate positive electrode materials that cannot be directly reused due to capacity attenuation will need to be efficiently recycled and regenerated, which is crucial to the healthy development of the lithium-ion battery industry. At present, the main recycling processes for retired lithium iron phosphate positive electrode materials are metallurgical method and direct regeneration method.
[0003] There are two main metallurgical methods: pyrometallurgy and hydrometallurgy. Pyrometallurgy recycling mainly involves crushing and calcining the dismantled waste cathode materials to collect the metal elements. The price of the valuable metal element Fe in lithium iron phosphate is relatively low, and the pyrometallurgical recycling has high energy consumption and cannot achieve profit-driven. The hydrometallurgical recycling process uses a large amount of acid and alkali to leach and extract the lithium and iron elements in lithium iron phosphate, which will cause secondary pollution and trigger new environmental problems.
[0004] The direct regeneration method is different from the traditional metallurgical recycling method. It does not need to destroy the original structure of the waste lithium iron phosphate positive electrode material, retains its inherent intrinsic value, and only restores its chemical composition and microstructure by supplementing the element source and reducing and repairing. Invention patent CN201710446047.4 discloses a method for recycling retired lithium iron phosphate materials through direct repair and regeneration. First, the content of each element in the waste material is tested, and the corresponding lithium source, iron source or / and phosphorus source are supplemented to a molar ratio of lithium: iron: phosphorus of (1 to 1.05): 1: 1, and the regenerated lithium iron phosphate is obtained by high-temperature roasting under an inert atmosphere. The process is simple and the recycled product has high added value, but it still has the disadvantages of complex material element missing amount testing, low lithium replenishment efficiency and high energy consumption, which makes it difficult to meet the needs of large-scale recycling. Summary of the invention
[0005] In view of this, the present invention provides a method for repairing retired lithium iron phosphate positive electrode materials, which overcomes the problems of the existing retired lithium iron phosphate positive electrode material recycling process, such as complicated procedures, high energy consumption, easy to cause secondary pollution and low added value of recycled products.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention discloses a method for repairing retired lithium iron phosphate positive electrode materials, comprising the following steps:
[0008] S1, adding the first lithium salt and tea polyphenols into a solvent and fully dissolving them to obtain a repair solution;
[0009] S2. Add the retired lithium iron phosphate cathode powder into the repair solution and mix evenly to obtain a suspension;
[0010] S3, heating the suspension to react, performing solid-liquid separation after cooling, washing and drying the solid product, and collecting the separated liquid for later use;
[0011] S4, mixing the dried solid product with aluminum salt, phosphate ions, and a second lithium salt in a solvent, heating and stirring until the water is evaporated, and annealing in an inert atmosphere to obtain a repaired lithium iron phosphate positive electrode material; in this step, aluminum ions (Al 3+ ) and phosphate ions (PO4 3- ) reacts to form aluminum phosphate (AlPO4); while lithium ions (Li + ) and phosphate ions (PO4 3- ) react to form aluminum phosphate (Li3PO4); after final annealing, an aluminum phosphate / lithium phosphate filling coating layer is formed at the missing carbon layer on the surface of the repaired lithium iron phosphate;
[0012] S5. Use the liquid collected in step S3 as a repair solution and repeat steps S2-S4 to repair the next batch of retired lithium iron phosphate positive electrode materials.
[0013] Among them, tea polyphenols are extracted from tea leaves or artificially synthesized, the retired lithium iron phosphate positive electrode powder is a powder obtained by discharging, disassembling, peeling, crushing and separating waste power or energy storage lithium iron phosphate battery materials; the inert atmosphere is nitrogen, argon, and a nitrogen-argon mixed gas; preferably, the inert atmosphere is nitrogen.
[0014] A further solution: in step S1, the first lithium salt is at least one of lithium hydroxide, lithium nitrate and lithium acetate; and / or:
[0015] In step S4, the second lithium salt is at least one of lithium carbonate, lithium sulfate, and an organic lithium compound. The trace amount of the second lithium salt added in step S4 is mainly to offset the lithium volatilized during high temperature annealing and to supplement the lithium source for the system, which is conducive to further generating fast ion conductor Li3PO4 and satisfying the good Li + Transmission requirements.
[0016] In step S4, the second lithium salt is at least one of lithium carbonate, lithium sulfate, and an organic lithium compound; and / or:
[0017] In step S4, the aluminum ions are derived from aluminum nitrate, aluminum chloride, aluminum sulfate or aluminum silicate, and the phosphate ions are derived from ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
[0018] A further solution: In step S1, the concentration of the first lithium salt in the repair solution is 0.15-0.25 mol / L, and the concentration of tea polyphenols is 0.08-0.12 mol / L.
[0019] A further solution: In steps S1 and S4, the solvent is a mixture of deionized water and ethanol.
[0020] A further solution: In step S2, the solid-liquid ratio of the retired lithium iron phosphate positive electrode powder and the natural green reducing repair agent is 0.01-0.02 g / mL.
[0021] Further scheme: in step S3, the heating reaction temperature is 100-120° C. and the time is 8-12 hours; and / or:
[0022] In step S3, the precipitate is washed and dried by: washing and filtering the precipitate alternately and repeatedly with deionized water and anhydrous ethanol, and drying the precipitate at 80-100° C. for 8-10 hours.
[0023] A further solution: in step S4, the annealing temperature is 600°C-700°C, the annealing time is 4h-6h; and / or the annealing heating rate is 3°C / min-5°C / min.
[0024] A further solution: In step S4, the mass ratio of the precipitate, aluminum nitrate, ammonium dihydrogen phosphate, and the second lithium salt is 200:(6.2-31):(1.9-9.5):4.
[0025] In a second aspect, the present invention discloses a lithium iron phosphate positive electrode material, which is obtained by the above-mentioned repair method.
[0026] In a third aspect, the present invention discloses a lithium battery, wherein the positive electrode material of the lithium battery comprises a lithium iron phosphate positive electrode material obtained by the above-mentioned repair method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The direct repair and upgrading method of retired lithium iron phosphate positive electrode materials provided in the present invention uses tea polyphenols extracted naturally from abundant tea leaves as electron donors. The multiple hydroxyl groups of tea polyphenols can repair the structural defects of waste lithium iron phosphate and create a good reducing environment for it. Together with the supplemented lithium salt, it not only helps to convert the decayed FePO4 phase in the waste lithium iron phosphate into a single LiFePO4 phase, but also helps to eliminate harmful Li-Fe anti-site defects; thereby rebuilding Li +Rapid diffusion channels are used to achieve repairs in composition and structure. At the same time, in order to address the damage and missing carbon layer on the surface of waste lithium iron phosphate, low-cost aluminum and phosphorus sources are introduced on the basis of the above, and the composite coating of AlPO4 with a stable structure and Li3PO4 that is conducive to ion transmission is filled in the damaged and missing carbon layer on the surface of the repaired lithium iron phosphate. The upgraded and regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate can meet the requirements of low cost and high performance in various applications. Compared with the introduction of carbon sources on the surface of waste lithium iron phosphate to form a new carbon layer, the aluminum phosphate / lithium phosphate composite, relying on its preferential binding with lithium iron phosphate, accurately forms a composite filling coating of amorphous AlPO4 and Li3PO4 grains at the damaged carbon layer and the exposed active material, which can achieve targeted filling of the damaged and missing carbon layer on the surface of waste lithium iron phosphate, and help to improve the overall energy density of lithium iron phosphate positive electrode materials. The AlPO4 filling coating is amorphous and contains Li3PO4 grains of fast ion conductors, which will provide a fast lithium ion transmission channel on the surface of the active material while stabilizing the structure, which is beneficial to improving the rate performance of lithium iron phosphate after regeneration.
[0029] The present invention provides a green repair and upgrading method for retired lithium iron phosphate positive electrode materials. The process does not require secondary treatment of the waste lithium iron phosphate materials to destroy the structure, and does not require testing to determine its element content. It directly uses a natural green reductive repair agent to restore its chemical composition and crystal structure, and at the same time coats it with a low-cost coating layer to upgrade the electrochemical performance and value of the regenerated product. The natural green reductive repair agent used in the method of the present invention can be recycled, the process is simple and environmentally friendly, and the cost is low and easy to promote on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the process for upgrading, repairing and regenerating waste lithium iron phosphate;
[0031] Figure 2 XRD spectra of unrepaired waste lithium iron phosphate and the lithium iron phosphate repaired in comparative example 1 and upgraded and regenerated in examples 1-3;
[0032] Figure 3 Comparison of HAADF-STEM images of waste lithium iron phosphate particles and the repaired lithium iron phosphate in Example 1;
[0033] Figure 4 This is the TEM image of waste lithium iron phosphate particles;
[0034] Figure 5 The TEM image and surface element distribution spectrum of the lithium iron phosphate after repair in Example 1;
[0035] Figure 6This is a comparison chart of the cycle performance of unrepaired waste lithium iron phosphate and the repaired lithium iron phosphate of Example 1-3 and Comparative Example 1-2 at 2C for 300 times. DETAILED DESCRIPTION
[0036] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0038] The raw materials used in the examples and comparative examples are all commercially available conventional products.
[0039] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0040] Example 1
[0041] S1: 0.3 g of lithium hydroxide monohydrate and 1.6 g of tea polyphenols are completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0042] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0043] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0044] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 18.5 mg of aluminum nitrate nonahydrate and 5.7 mg of ammonium dihydrogen phosphate, add 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate positive electrode material;
[0045] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0046] Example 2
[0047] S1: 0.3 g of lithium hydroxide monohydrate and 1.6 g of tea polyphenols are completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0048] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0049] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0050] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 6.2 mg of aluminum nitrate nonahydrate and 1.9 mg of ammonium dihydrogen phosphate, and add 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate-coated lithium iron phosphate positive electrode material;
[0051] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0052] Example 3
[0053] S1: 0.3 g of lithium hydroxide monohydrate and 1.6 g of tea polyphenols are completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0054] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0055] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0056] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 31 mg of aluminum nitrate nonahydrate and 9.5 mg of ammonium dihydrogen phosphate, add 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate positive electrode material;
[0057] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0058] Example 4
[0059] S1: 0.72 g lithium acetate dihydrate and 1.6 g tea polyphenols were completely dissolved in a mixed solvent of 30 mL deionized water and 5 mL anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0060] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0061] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0062] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 18.5 mg of aluminum nitrate nonahydrate and 5.7 mg of ammonium dihydrogen phosphate, add 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate positive electrode material;
[0063] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0064] Example 5
[0065] S1: 0.3 g of lithium hydroxide monohydrate and 1.6 g of tea polyphenols are completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0066] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0067] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0068] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 18.5 mg of aluminum nitrate nonahydrate and 5.7 mg of ammonium dihydrogen phosphate, add 4 mg of lithium sulfate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate positive electrode material;
[0069] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0070] Comparative Example 1
[0071] S1: 0.3 g of lithium hydroxide monohydrate and 1.6 g of tea polyphenols are completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a natural green direct reduction repair agent solution;
[0072] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0073] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0074] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain a repaired and regenerated lithium iron phosphate positive electrode material;
[0075] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0076] Comparative Example 2
[0077] S1: 0.3 g of lithium hydroxide monohydrate is completely dissolved in a mixed solvent of 30 mL of deionized water and 5 mL of anhydrous ethanol to obtain a repair agent solution;
[0078] S2: Mix 0.55 g of retired lithium iron phosphate positive electrode material powder and the natural reduction repair agent solution in step S1 to obtain a mixed suspension;
[0079] S3: the suspension in step S2 is placed in a reaction kettle and heated to 120°C in an oven for 10 hours. After cooling, the precipitate is collected and washed and filtered repeatedly with deionized water and anhydrous ethanol, and then dried in a drying oven at 90°C for 8 hours.
[0080] S4: Take 0.2 g of the precipitate dried in step S3, mix it with 18.5 mg of aluminum nitrate nonahydrate and 5.7 mg of ammonium dihydrogen phosphate, add 4 mg of lithium carbonate, add it into a mixed solvent of 20 ml of deionized water and a small amount of anhydrous ethanol, heat it to 90° C. and stir it at a speed of 400 rpm until it is completely evaporated to dryness, and after evaporation, anneal it at 600° C. for 5 h under nitrogen to obtain an upgraded regenerated aluminum phosphate / lithium phosphate coated lithium iron phosphate positive electrode material;
[0081] S5: The repair agent solvent separated in step S3 is recovered and can be recycled for repairing and regenerating the next batch of retired lithium iron phosphate positive electrode materials.
[0082] Performance testing and result analysis
[0083] 1. Material Characterization
[0084] Figure 1 The schematic diagram of the process of upgrading, repairing and regenerating waste lithium iron phosphate is shown. First, in view of the large number of lithium vacancies and Li-Fe anti-site defects and the inactivated irreversible FePO4 phase in the crystal structure of waste lithium iron phosphate particles, the present invention provides a driving force through hydrothermal treatment, uses natural and environmentally friendly tea polyphenols as electron donors, provides a suitable reducing environment, reduces trivalent iron to divalent iron, and combines with supplementary lithium salts to repair defects in the crystal structure and convert the irreversible FePO4 phase into an electrochemically active LiFePO4 phase. Secondly, in view of the problem of damaged and missing carbon layers on the surface of waste lithium iron phosphate particles, the present invention introduces cheap aluminum sources and phosphorus sources in the post-annealing stage, and utilizes the characteristics of aluminum phosphate / lithium phosphate that preferentially combines with bare lithium iron phosphate compared to carbon, and fills the damaged and missing carbon layers in a targeted manner to form a composite coating of amorphous aluminum phosphate and fast ion conductor lithium phosphate, thereby improving structural stability without reducing the energy density of active materials.
[0085] Figure 2The XRD spectra of the unrepaired waste lithium iron phosphate and the lithium iron phosphate repaired in comparative example 1 and upgraded and regenerated in examples 1-3 are shown; it can be seen that in addition to the LiFePO4 phase, the unrepaired waste lithium iron phosphate phase has an obvious deactivated irreversible FePO4 phase, which is the reason for the attenuation of its electrical performance. In comparative example 1 and examples 1-3, tea polyphenols are used as electron donors in combination with lithium salts, and the irreversible FePO4 phase has been completely converted into an electrochemically active LiFePO4 phase through hydrothermal treatment. However, the problem of the missing carbon layer on the surface of the lithium iron phosphate in comparative example 1 has not been effectively solved, while in examples 1-3, with the increase in the amount of aluminum source and phosphorus source, it can be seen that the fast ion conductor Li3PO4 phase is generated, and the AlPO4 phase has no corresponding peaks observed in the XRD spectrum due to its amorphous structure. They are precisely filled in the missing carbon layer to repair the coating.
[0086] Figure 3 The high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) images of the waste lithium iron phosphate particles and the repaired lithium iron phosphate of Example 1 are compared. There are a large number of damages and cracks on the surface of the waste lithium iron phosphate waste powder particles, and the carbon layer is obviously damaged, while the microcracks on the surface of the repaired lithium iron phosphate particles are repaired, and the particles are relatively round because the damaged parts are filled with coating.
[0087] Figure 4 The TEM image of waste lithium iron phosphate particles is shown, and it can be seen that there is an obvious transition from the LiFePO4 phase through the amorphous disordered region to the deactivated irreversible FePO4 phase in the crystal structure of waste lithium iron phosphate. These deactivated irreversible FePO4 phases are an important factor in the attenuation of its electrochemical performance.
[0088] Figure 5 The TEM image and surface element distribution spectrum of the lithium iron phosphate after repair in Example 1 are given. It can be seen that amorphous AlPO4 is distributed on the surface of the lithium iron phosphate block, and the fast ion conductor Li3PO4 phase is embedded in the amorphous AlPO4, while the interior of the block is a uniform LiFePO4 phase, and the irreversible deactivated FePO4 phase has been completely eliminated. The element distribution spectrum shows that there are Al and P signals on the particle surface, which further verifies the coating filling of the surface amorphous AlPO4, and the Al element signal and C element signal intensity are alternately distributed, indicating that the amorphous AlPO4 coating can target and fill the missing carbon layer.
[0089] 2. Electrochemical performance
[0090] Figure 6Figure 1 shows the electrochemical performance of the unrepaired waste lithium iron phosphate and the repaired lithium iron phosphate of Example 1 and Comparative Examples 1-2 after 400 cycles at 2C. It can be seen that compared with the waste lithium iron phosphate (the specific capacity is basically zero after 400 cycles at 2C), the repaired and regenerated lithium iron phosphate in Example 1 has a significantly improved specific capacity at a high current density of 2C (the specific capacity is 124.3 mAhg after 400 cycles at 2C). -1 ), restored to the specific capacity level of fresh lithium iron phosphate electrode materials, and the cycle stability was also greatly improved (400 cycles capacity retention rate at 2C was 92.1%); while the lithium iron phosphate in comparative example 1 only repaired the defects in the composition and crystal structure by combining tea polyphenols as electron donors with lithium salts, but the carbon missing and damaged parts on the surface were not improved, and the exposed lithium iron phosphate was prone to side reactions in the electrolyte. Therefore, although the specific capacity was repaired and improved a lot, its capacity retention rate was very low. In comparative example 2, although the ingredients were supplemented and the carbon missing and damaged parts on the surface were filled with AlPO4 / Li3PO4, the lithium iron anti-site defects in the crystal structure and the inactivated irreversible FePO4 phase were not well repaired and improved, so the electrical performance was not good. Figure 6 b shows the electrochemical performance of the repaired lithium iron phosphate of Examples 1-3 after 400 cycles at 2C. It can be seen that when the amount of Al and P source used in Example 2 is small, the specific capacity is higher, but the improvement in cycle stability is limited; and when the amount of Al and P source used in Example 3 is large, the specific capacity is sacrificed more, so the amount of Al and P source used in Example 1 is optimal.
[0091] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0092] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A method for repairing retired lithium iron phosphate positive electrode materials, characterized in that: The following steps are involved: S1, adding the first lithium salt and tea polyphenols into a solvent and fully dissolving them to obtain a repair solution; S2. Add the retired lithium iron phosphate cathode powder into the repair solution and mix evenly to obtain a suspension; S3, heating the suspension to react, performing solid-liquid separation after cooling, washing and drying the solid product, and collecting the separated liquid for later use; S4, mixing the dried solid product with aluminum ions, phosphate ions, and a second lithium salt in a solvent, heating and stirring until the water is evaporated, and annealing in an inert atmosphere to obtain a repaired lithium iron phosphate positive electrode material; S5. Use the liquid collected in step S3 as a repair solution, repeat steps S2-S4, and continue to repair the next batch of retired lithium iron phosphate positive electrode materials.
2. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S1, the first lithium salt is at least one of lithium hydroxide, lithium nitrate and lithium acetate; and / or: In step S4, the second lithium salt is at least one of lithium carbonate, lithium sulfate, and an organic lithium compound; and / or: In step S4, the aluminum ions are derived from aluminum nitrate, aluminum chloride, aluminum sulfate or aluminum silicate, and the phosphate ions are derived from ammonium dihydrogen phosphate or diammonium hydrogen phosphate.
3. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S1, the concentration of the first lithium salt in the repair solution is 0.15-0.25 mol / L, and the concentration of tea polyphenols is 0.08-0.12 mol / L.
4. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In steps S1 and S4, the solvent is a mixture of deionized water and ethanol.
5. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S2, the solid-to-liquid ratio of the retired lithium iron phosphate positive electrode powder to the repair solution is 0.01-0.02 g / mL.
6. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S3, the heating reaction temperature is 100-120° C. and the time is 8-12 hours; and / or: In step S3, the precipitate is washed and dried by: washing and filtering the precipitate alternately and repeatedly with deionized water and anhydrous ethanol, and drying the precipitate at 80-100° C. for 8-10 hours.
7. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S4, the annealing temperature is 600°C-700°C, the annealing time is 4h-6h, and the annealing heating rate is 3°C / min-5°C / min.
8. The method for repairing retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step S4, the mass ratio of the precipitate, aluminum nitrate, ammonium dihydrogen phosphate, and the second lithium salt is 200:(6.2-31):(1.9-9.5):
4.
9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is obtained by processing the repair method according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: The positive electrode material of the lithium battery comprises a lithium iron phosphate positive electrode material obtained by the repair method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A method for recycling and repairing lithium iron phosphate materials
CN107275705B
Surface modification method of high-nickel ternary material lithium nickel cobalt manganate
CN109920993A
Method for recycling nickel-cobalt-manganese waste ternary lithium battery positive electrode material
CN111180822A
Preparation method of positive electrode material with surface coated with phosphate fast ion conductor
CN117855450A
Method for recycling waste lithium iron phosphate battery to generate lithium iron manganese phosphate positive electrode material
CN117977038A
Cited By
Regeneration method of retired lithium iron phosphate material and regenerated lithium iron phosphate
CN121355446A